National survey of prevention and management of CMV infection in pediatric kidney transplantation in comparison to clinical practice guidelines - Madden, Iona; Baudouin, Véronique; Charbit, Marina; Ranchin, Bruno; Roussey, Gwenaëlle; Novo, Robert; Garaix, Florentine; Decramer, Stéphane; Fila, Marc; Merieau, Elodie; Vrillon, Isabelle; Zaloszyc, Ariane; et al. (Frontiers in Pediatrics, 2022)
Background. Cytomegalovirus (CMV) is one of the most frequent opportunistic infections in kidney transplant (KT) recipients and is a risk factor for patient and graft survival after KT. Center-to-center variation, optimal prevention and treatment strategies in pediatric KT are currently unknown. This survey aimed to assess current CMV prevention and treatment strategies used among French pediatric KT centers. Methods. A web-based survey was sent to all 13 French pediatric kidney transplantation centers. Results. Twelve (92%) centers responded to the survey. All centers used prophylaxis for the donor-positive/recipient-negative (D+/R-) group. For R+ patients, 54% used prophylaxis, 37% used a pre-emptive strategy. In the low-risk group, D-/R-, 50% used a pre-emptive approach and 50% had no specific prevention strategy. The antiviral used by all centers for prophylaxis was valganciclovir (VGCV). The duration of prophylaxis varied from 3 to 7 months and the duration of viral load monitoring varied from 6 months to indefinitely. No center used a hybrid/sequential approach. For the treatment of CMV DNAemia, VGCV or intravenous GCV were used. Therapeutic drug monitoring of VGCV was performed in 5 centers (42%). Five centers reported drug resistance. Eight centers (67%) administered VGCV during the treatment of acute graft rejection. Conclusions. There is uniformity in CMV management in some areas among pediatric KT centers in France but not in others which remain diverse and are not up to date with current guidelines, suggesting unnecessary variation which could be reduced with better evidence to inform practice.